REPRODUCTIVE CYCLE AND CHANGES IN ASSOCIATED PARTS OF GONAD IN CRASSOSTREA (SACCOSTREA) GLOMERATA (GOULD) FROM THE COAST OF KARACHI - Asif, M (Indian Journal of Fisheries, 2011)
A study of the reproductive cycle of Crassestrea (Saccostrea) glomerata from the coast of Karachi is described for the years 1971-73. The species attains maturity of gonad in majority of specimens in April, which is continued in fluctuating manner through October. Active spawning continues from MaylJune to November. Comparison among the different size groups shows that spawning in youngest size group is very restricted, which may be attributed to abundance of phagocytes throughout the year. No ’inactive phase’ is observed but ’indifferent phase’ generally occurs in winter. Comparison with the same Sipecies of New Zealand shows that the temperature range at which reproduction is carried out is different from that of the latter locality, suggesting acclimatisation to different temperature condition of the two areas. Glycogen granules were abundant in winter which declined gradually reaching minimum value in May|June and this condition remained in summer. In September, build of glycogen starts, which attained maximum concentration in the body parts in winter (November through January). In conclusion the observations on the reproductive cycle of the species from Karachi shows a different pattern from those of temperate regions.